Contractility as a global regulator of cellular morphology, velocity, and directionality in low-adhesive fibrillary micro-environments. (September 2016) - Schuster, Simon L.; Segerer, Felix J.; Gegenfurtner, Florian A.; Kick, Kerstin; Schreiber, Christoph; Albert, Max; Vollmar, Angelika M.; Rädler, Joachim O.; Zahler, Stefan
Abstract: Recent reports demonstrated that migration in fibrillary environments can be mimicked by spatial confinement achieved with micro-patterning [1]. Here we investigated whether a model system based on linearly structured surfaces allows to draw conclusions about migration of endothelial cells (ECs) in fibrillary 3D environments. We found that ECs on 3 μm wide tracks (termed as 1D) migrate less efficient in comparison to ECs on broader tracks in regard to velocity and directional persistence. The frequent changes of direction in ECs on narrow tracks are accompanied by pronounced cell rounding and membrane blebbing, while cells migrating with an elongated morphology display a single lamellipodium. This behavior is contractility-dependent as both modes can be provoked by manipulating activity of myosin II (blebbistatin or calyculin A, respectively). The comparison between 1D and 3D migrating cells revealed a striking similarity in actin architecture and in switching between two morphologies. ECs move more directed but slower upon inhibition of contractility in 1D and 3D, in contrast to 2D cell culture. We conclude that micro-patterning can be used to study morphological switches in a controlled manner with a prognostic value for 3D environments. Moreover, we identified blebbing as a new aspect of EC migration.